Sistem Pakar untuk Penyakit Anak Menggunakan Metode Forward Chaining - Suwarso, Gideon Abram Filando; Budhi, Gregorius Satia; Dewi, Lily Puspa (Jurnal Infra, 2015)
The main study in this thesis is the design and the development of an expert system with forward chaining and backward chainingmethod. In this thesis, uses the children common disease due tothe body immune in young children is not as good and perfect as adultâs. This makes children to be infected easily.The method used in the development of this expert system isforward chaining and backward chaining, which is driven by the facts that exist. The facts obtained from the patients physical condition, or so-called symptoms. In making this expert system knowledge is required excavation by an expert engineer from the expert of the subject, in this case is a doctor. The process of extracting knowledge by means of interviews.Based on the analysis, this expert system has a percentage of program eligibility to be used by common people is at 85.4%. Moreover about the ease of usage this program also get a high percentage.